The Impact of Culture, Fit, and Work-Life Balance on Retention: The Mediating Role of Commitment at PT Madubaru - Gita Danupranata; Anfasa Praditaningrum (Riwayat: Educational Journal of History and Humanities, 2025)
This study identifies the mediating role of organizational commitment in the influence of organizational culture, person-organization fit, and work-life balance on intention to stay among employees of PT Madubaru PG/PS Madukismo. This research employs a quantitative approach using a non-probability sampling technique, specifically convenience sampling. Data was collected through the distribution of questionnaires to 160 respondents and analyzed using Structural Equation Modeling (SEM) with SmartPLS version 3.0 software. Based on the analysis results, organizational culture has a positive and significant effect on organizational commitment, organizational culture has a positive and significant effect on intention to stay, organizational commitment has a positive and significant effect on intention to stay, person-organization fit has a positive and significant effect on organizational commitment, person-organization fit has a positive and significant effect on intention to stay, work-life balance has a positive and significant effect on organizational commitment, work-life balance has a positive and significant effect on intention to stay, organizational commitment mediates the effect of organizational culture on intention to stay, organizational commitment mediates the effect of person-organization fit on intention to stay, and organizational commitment mediates the effect of work-life balance on intention to stay.This study aims to expand the existing literature by examining the mediating role of organizational commitment in the influence of organizational culture, person-organization fit, and work-life balance on intention to stay. The results of this study provide insights for practitioners and policymakers in organizations to enhance employees' intention to stay. By building a strong organizational culture, improving person-organization fit, and supporting work-life balance, companies can strengthen employees' organizational commitment. This increased commitment can ultimately reduce turnover and create a more stable and productive work environment.